The Vaccine-Education Paradox in a Cross-Country Analysis: Education Predicts Higher and Lower Vaccination Rates - Radosław Trepanowski; Dariusz Drążkowski (SAGE Open, 2024)
Research has shown a mixed relationship between education and vaccination rates. In the current analysis, we aimed to determine the relationship between educational level and coronavirus disease 2019 (COVID-19) vaccination rates. We performed a cross-country analysis on data from 133 countries. Correlation analyses showed that higher and better education was associated with higher COVID-19 vaccination rates. When we performed the regression analysis including the education, health system, and economic development variables, education-COVID-19 vaccination relationships were mostly reversed. In particular, in wealthy countries, as the mean years of schooling decreased and the pupil-teacher ratio increased, COVID-19 vaccination rates increased. In less affluent countries, with greater education expenditures, COVID-19 vaccination rates decreased. We explain these contradictions by describing links between vaccination rates, life expectancy, and education-related variables. Our findings may aid in promoting more effective uptake of COVID-19 vaccination.